PERANAN PERKEBUNAN KARET DALAM PEMBANGUNAN EKONOMI WILAYAH DI KABUPATEN MUARO JAMBI - Elwamendri; Fitri Dianti, Eka; Mara, Armen (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2021)
This Research aims to determine the development of the rubber plantations in Jambi Muaro, knowing developments in construction area Muaro Jambi and determine the role of rubber plantations in the construction area in Jambi Muaro. Method of data analysis is descriptive analysis, microsoft excel application and analysis of a sector basis using the formulations Location Quotient (LQ), contribution analysis, shift share analysis and analysis of short-term multiplier. Based on the analysis that has been done shows that the development of rubber plantations in Muaro Jambi based on land area and production has increased trend, but based workforce is impaired. The development GDP growth rate increased Muaro Jambi. Then the rubber plantations in Muaro Jambi is the basis for sectors Muaro Jambi based on GDP at constant prices and GDP at current prices. But not a basis for indicators of sector workforce Muaro Jambi.